Georgia Education Sector Policy Review : Strategic Issues and Reform Agenda - World Bank (World Bank, Washington, DC, 2017)
The scope and pace of education reforms in Georgia over the last decade are unique in the region but have not yet yielded the expected improvements in the quality of education. In particular, reforms of financing and governance of educational institutions, that other countries have been grappling with for years, have been implemented. The key reforms included: (i) the decentralization of the management; (ii) the adoption of a per-student financing mechanism at all levels of education; (iii) the creation, under the umbrella of the ministry of education and science, of new public legal entities responsible for ensuring the quality of reforms; (iv) the adoption of new standards and outcome-based national curricula in general education along with the development of new textbooks; and (v) the design of a new national assessment and examination system. The government has set a clear vision for the future of the education sector as a tool for human capital development to support economic growth. To achieve the new vision for the sector s development, the government needs to address the remaining challenges both at the system and sub-sector level. The analysis presented in this report reveals that the major challenge across all levels of education in Georgia is improving quality and, more specifically, improving student outcomes. The document presents comparative analysis and brings in relevant examples from other countries and country comparisons for that purpose.